Rescuing traditional medicine in maternal and child health in the afrocaucanas communities through intercultural dialogue - Portela Guarín, Hugo; Astaiza Bravo, Nohra Ximena; Guerrero Pepinosa, Nancy Yadira; Rodríguez Guarín, Salomón (Universidad y Salud, 2013)
This paper is based on theoretical models and documentaries to propose intercultural dialogue as a strategy to rescue traditional medicine in Maternal Child Health (MCH) of afrocaucanas communities. The recognition of cultural aspects in health promotes the ability of biomedical agents in the timely intervention based on renewed models of Primary Health Care (PHC). In this context, the high rates of maternal and child morbidity and mortality in the vulnerable afrocaucanas communities show the low social development of Cauca department and the lack of relevant strategies to care vulnerable population. This situation leads to the need to renew PHC models from an intercultural approach that promotes the traditional medicine of these communities. State, biomedical and academic recognition of traditional medicine in MCH allows the rescue of cultural and ethnic identity and at the same time contributes to the search for alternatives in health based on intercultural dialogue. Therefore, it is imperative to build dialogue to rescue traditional knowledge and practices in MCH as a form of inclusive participation and development factor for the department.